TRANSLATION SHIFTING ON MAHFUDZOT SUBJECT IN ISLAMIC BOARDING SCHOOL - Rohany, Siti; Kumala, Sonya Ayu; Beata Sitindjak, Shenny Ayunuri (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2024)
The conceptual of translation between Arabic and Indonesian, a language path replete with nuanced cultural details and grammatical complexity. By examining translation as a dynamic interaction between two different language systems, we hope to analyze the difficulties and solutions that arise while translating Arabic writings into Indonesian. This investigation seeks to add to the corpus of knowledge in translation studies by utilizing well-established translation theories and real-world case studies. This research aims to delve into the multifaceted nature of translation shifts, shedding light on the diverse strategies employed by translators to navigate linguistic and cultural disparities. In the quest for a deeper understanding of translation shifts, this journal will explore various theoretical frameworks and analytical approaches. This research aims to provide insights that are beneficial to researchers and practitioners by negotiating the distinct language terrain that exists between Arabic and Indonesian. The intention is to improve our understanding of the translation process for fruitful discussion of the subtleties unique to translating from Arabic to Indonesian.